Encyclopedia of Life Sciences 2021
DOI: 10.1002/9780470015902.a0029079
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of V1R Repertoires in Subterranean Rodents

Abstract: Pheromones are chemicals released and perceived by members of the same species, triggering sexual and social behaviours or physiological changes in diverse animals. Although rodents are the first mammals in which vomeronasal receptors and their major roles in pheromonal olfaction were identified, little is known about the evolution of vomeronasal receptor gene repertoires in subterranean rodents. Recent genome‐wide surveys in rodents have shown that the number of functional vomeronasal type 1 receptor ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…While V1Rs are mainly involved in detecting air-borne molecules scattered in the air, V2Rs are commonly responsible for binding to water-soluble peptides abundant in aquatic environments ( Shi and Zhang, 2007 ). Recently, it was shown that there has been a convergent reduction of V1Rs in different subterranean rodents, including the BMR ( Jiao et al, 2019 ; Zhao, 2021 ), suggesting that pheromonal olfaction mediated by V1Rs might be reduced, as it may not be as useful as seismic communication in the underground tunnel environment.…”
Section: Introductionmentioning
confidence: 99%
“…While V1Rs are mainly involved in detecting air-borne molecules scattered in the air, V2Rs are commonly responsible for binding to water-soluble peptides abundant in aquatic environments ( Shi and Zhang, 2007 ). Recently, it was shown that there has been a convergent reduction of V1Rs in different subterranean rodents, including the BMR ( Jiao et al, 2019 ; Zhao, 2021 ), suggesting that pheromonal olfaction mediated by V1Rs might be reduced, as it may not be as useful as seismic communication in the underground tunnel environment.…”
Section: Introductionmentioning
confidence: 99%